Heavy metal removal by biopolymers-based formulations with native potato starch/nopal mucilage - Choque Quispe, David (2020)
The contamination of water bodies by heavy metals is a critical problem for human health and ecosystems, and it can bioaccumulate in organisms to toxic levels and even lead to the living being’s death. This research aimed to synthesize and characterize a biopolymer with the capacity to remove heavy metals in wastewater, elaborated from potato starch, glycerin, and nopal mucilage. Native potato starch of the Allcca sipas variety was extracted by conventional methods; the mucilage was extracted with ethanol. Four formulations of biopolymers were synthesized at 60 and 70 °C. The solubility, structural characteristics, and adsorption capacity of heavy metals were evaluated. Starch, mucilage, and biopolymers presented predominant functional groups as -OH, -C-O-, -NH-, -C-H-, -C-OH determined by FTIR, allowing to remove up to 50.18% of Al, 56.81% of As, 35.95% of Cr, 37.43% of Hg and 73.22% of Pb determined through an ICPE-OES, for a contact time of 100 minutes at pH 5.0, heavy metal removal and solubility were significantly influenced (p-value < 0.05) by the addition of starch and mucilage. The synthesized biopolymers present a high capacity for heavy metal removal in wastewater